To Assess the Knowledge Attitude & Perception Towards Informed Consent Among Medical Students, Navi Mumbai (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
Informed consent is a fundamental ethical and legal requirement in medical practice in both the field of research and therapeutics This ensures that patients are made aware of and agree to the proposedintervention. Medical students at all levels of education are taught to provide clear and understandable information about the risks, benefits, and alternatives to patients, allowing them to make autonomous and informed decisions. A cross-sectional study assessed knowledge, attitudes, and perceptions regarding informed consent among medical students in and across Navi Mumbai. A cross-sectional,observational, questionnaire-based study was conducted using a validated questionnaire.
Keywords: Informed consent; negligence; medical ethics; CBME curriculum